Evolution in hemophilia treatment - Natesirinilkul, Rungrote (Biomedical Sciences and Clinical Medicine, 2024)
Objective Even though hemophilia has been known since the ancient time, the understanding of disease and proper management of hemophilia have just been established for 50 years. After the discovery of cryoprecipitate, which was a big step of hemophilia therapy, between 1950-1960, the therapy of hemophilia has been advancing progressively, including the usage of factor concentrate and desmopressin for on-demand and prophylactic treatment, the development of bypassing agent for hemophiliac patients with inhibitor, the production of long-acting factor concentrate and gene therapy in hemophiliac patients. This knowledge of hemophilia treatment is interesting and worth following in the future.